Sample Processing Methods Impacts on Rumen Microbiome - Martinez-Fernandez, Gonzalo; Denman, Stuart E.; McSweeney, Christopher S. (Frontiers in Microbiology, 2019)
The standardization of collection and processing methods for rumen samples is crucial to reduce the level of errors that may affect the analysis and interpretation of the data. The aim of this study was to compare two processing methods and their impacts on the microbial community composition analysis, from material that was either immediately frozen or samples that were stored as cell pellets after removing the supernatant prior to freezing. Eight rumen-fistulated Brahman steers received chloroform as an antimethanogenic compound for 21 days. Rumen fluid samples (60 mL per animal) were collected using a probe covered with two layers of cheesecloth at 3 h post feeding at day 0 prior-treatment (control period) and day 21 of treatment. One sub-set of samples were placed in dry ice and stored at −80◦C (Method 1) for subsequent DNA extraction, while a second subset of samples was centrifuged, the supernatant removed and the microbial pellet and rumen contents placed in dry ice and stored at −80◦C (Method 2) prior to DNA extractions. Phylogenetic based methods (Illumina Miseq) targeting the 16S rDNA gene were used to characterize the bacterial and archaeal communities from both collection methods for the control and treatment periods. The results from this study showed that the chloroform treatment was significantly different for all beta diversity measures regardless of the processing method used. Significant differences in the relative abundances of some bacteria and archaea, such as Elusimicrobia, Fibrobacteres, Lentisphaerae, Spirochaetes, and Verrucomicrobia and Methanomassiliicoccaceae, were observed at higher levels in the Method 2. These microbial populations are known to have fragile cell wall structures and are susceptible to cell lysis. Regardless of the processing method used, both identified the key microbial groups and can be used to compare the relative shifts in the rumen microbiome between treatments. However, immediately freezing samples might alter the abundance of material from species that are more readily lysed and will not be suitable for studies that aim to assign absolute abundance values to these species within the rumen.